THE EFFECTIVENESS OF USING SOCIAL MEDIA YOUTUBE IN IMPROVING THE SPEAKING SKILL OF THE FIRST GRADE STUDENTS OF SMA NEGERI 2 GOWA - Gifari, Nursyamri; Muliati, Andi; Talib, Ahmad (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The  objective  of  this  research  was  to  find  out  whether  the  use  of  social  media  YouTube  is effective  in  improving  the  speaking  skill  of  the  first-grade  students  of  SMA  Negeri  2  Gowa. This  research  took  place  at  SMA  Negeri  2  Gowa.  The  population  of  this  research  was  the students  of  SMA  Negeri  2  Gowa.  The  researcher  used  purposive  sampling  technique.  The instrument of this research was a speaking test which was administered as a pre-test and post- test. Based on the result  of the mean score,  the researcher found  that the use of social media YouTube  can  improve  students  speaking  abilities.  It  was  proved  by  the  result  of  the  post-test which  was  higher  than  result  of  the  pre-test  (29.11  >  46.06).  Furthermore,  the  researcher concluded that the use of social media YouTube effective in improving the speaking skill of the first-grade students of SMA Negeri 2 Gowa. Keywords— improving, social media YouTube, speaking skill